SYNTHESIS AND PHYSICAL-CHEMICAL PROPERTIESOF 3-ARIL-2-((3-(3-FLUORPHENYL)-1,2,4-TRIAZOLE-5-YL)THIO)PROP-2-EN-1-OLES - O. A. Bigdan; O. I. Panasenko; Ye. H. Knysh (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Modern scientific schools, which search for new biologically active substances of synthetic nature, pay special attention to synthetic heterocyclic systems with nitrogenatom. Among these heterocyclic compounds, the derivatives of 1,2,4-triazole should be mentioned. Many publications of both domestic and foreign scientists show prospects on active molecules search on the field of 1,2,4-triazolessubstituted. Due to good solubility and wide range of biological activity, such derivatives have gained popularityamong scientists around the world.